Reimaging Islamic Higher Education: PTKI’s Policy Directions and the Imperative of Digital Transformation - Fil Isnaeni; Hasnida (Yayasan Darusssalam Bengkulu, 2026)
Digital transformation has brought significant changes in the higher education system, including in Islamic Religious Universities (PTKI). This research aims to analyze the policy direction of PTKI in facing the challenges of digitization of education, with a focus on the integration of technology and Islamic values. The method used is qualitative research with a library research approach, with data sources in the form of the latest scientific articles (2021–2025) that are relevant to the research topic. The results of the study show that digital transformation in PTKI not only has an impact on the technical aspects of learning, but also includes changes in the paradigm of education, governance, and strengthening Islamic values. The ideal policy must be integrative, including strengthening the digital competence of human resources, developing technology-based learning, implementing digital governance, and integrating Islamic values in the education system. However, the implementation of these policies still faces various challenges, such as limited infrastructure, low digital literacy, and potential value disruption in the digital space. Therefore, a policy model that is adaptive, value-based, and oriented towards improving the quality of education holistically is needed. This research is expected to make a conceptual contribution to the development of relevant PTKI policies in the digital era